Teachers' Responsiveness to Preschoolers' Utterances in Sociodramatic Play. Issue 3 (2nd April 2016) - Meacham, Sohyun; Vukelich, Carol; Han, Myae; Buell, Martha
Abstract: Research Findings : This descriptive study used sequential analysis to examine both preschool teachers' responsiveness to children's utterances in sociodramatic play and the children's responses to their teachers' utterances. Eleven teachers in a Head Start program were videotaped while interacting with children in the dramatic play center. Salient findings of this study are threefold: (a) Teachers' responsiveness and the children's responsiveness to their teachers' talk varied substantially, (b) the children responded frequently to the teachers' topic-continuing utterances, and (c) the children responded frequently in the pretend play mode when teachers extended the children's utterances following the topics initiated by the children. Practice or Policy : The current study contributes to the extant research by providing a more fine-grained analysis of children's response modes in the sociodramatic play context. In addition, the current study suggests that teacher education and that practice and policies supporting teaching quality should consider emphasizing the details of teacher–child interaction in the dramatic play center at the utterance level.